Unionism, productive restructuring and finance capitalism - De Oliveira, Janaína [UNESP]; Jardim, Maria Chaves [UNESP]; Da Silva, Sidney Jard (FapUNIFESP (SciELO), 2021)
The article is part of contemporary discussions that challenge economic sociology and the sociology of work to reflect on a new socioeconomic phenomenon: The arrival of trade unionists in the financial market, through creation and, above all, the management of pension funds. Social actors of the construction of this new financial phenomenon, unionists come to (re)signify not only their strategies, but also their speeches, adding moral and social questions to the interests of the market. The work demonstrates that using the logic of capitalism itself in the fight against financialization of the economy and the productive restructuring would be the new ethos of Brazilian unionism.
Sindicalismo, reestruturação produtiva e capitalismo financeiro no Brasil
Keywords: Finance capitalism; Pension funds; Productive restructuring; Trade unions